Confined growth of multiple gold nanorices in dual-mesoporous silica nanospheres for improved computed tomography imaging and photothermal therapy - Qin L (Dove Medical Press, 2019)
Limei Qin,1 Dechao Niu,1 Yu Jiang,1 Jianping He,1 Xiaobo Jia,1 Wenru Zhao,1 Pei Li,2 Yongsheng Li1 1Laboratory of Low-Dimensional Materials Chemistry, Key Laboratory for Ultrafine Materials of Ministry of Education, School of Materials Science and Engineering, East China University of Science and Technology, Shanghai 200237, China; 2Department of Applied Biology and Chemical Technology, The Hong Kong Polytechnic University, Hong Kong, China Introduction: In this work, we have developed a novel “confined-growth” strategy to synthesize PEGylated multiple gold nanorices-encapsulated dual-mesoporous silica nanospheres (designated as PEGylated MGNRs@DMSSs) containing both small mesopores (2.5 nm) in the shell and large mesopores (21.7 nm) in the core based on a well-established, seed-mediated growth method. The photothermal effect and CT imaging ability were also studied.Methods: The nanoparticles were characterized by Fourier transform infrared (FT-IR) spectra, N2 absorption isotherms, Field-emission scanning electron microscopy (FE-SEM), Transmission electron microscopy (TEM), Inductively coupled plasma atomic emission spectroscopy (ICP-AES) and Confocal microscopy.Results: The longitudinally-localized surface (LSPR) absorption properties of MGNRs@DMSSs can be easily tuned by altering the amount of HAuCl4 in the gold growth solution. Additionally, the resultant PEGylated MGNRs@DMSSs have monodispersed, spherical morphology and good colloidal stability in an aqueous solution. More importantly, when exposed to NIR irradiation, the PEGylated MGNRs@DMSSs exhibit both higher temperature increments and better photothermal effects than that of single PEGylated gold nanorods at nearly an equivalent LSPR absorption. In addition, as CT contrast agents, the PEGylated MGNRs@DMSSs display a better CT imaging performance, in comparison with single PEGylated gold nanorods at the same Au concentration. Conclusion: Taken together, results indicate the potential for MGNRs@DMSSs used in CT imaging-guided photothermal therapy. Such a simple “confined-growth” strategy within a porous matrix offers a promising platform to design and prepare novel metal(s) oxide@silica nanocomposites for use in further cancer bio-imaging and therapy. Keywords: gold nanorices, dual-mesoporous silica, confined growth, imaging, photothermal effect